IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU PAI - Fauzi Ananda (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
The learning process and student learning outcomes are not only determined by the school, its pattern, structure and curriculum content, but are largely determined by the competence of the teachers who teach and guide them. Competent teachers will be better able to create an effective, fun learning environment, and will be better able to manage their classes, so that students' learning is at an optimal level. According to data from UNESCO in the 2016 Global Education Monitoring (GEM) Report, education in Indonesia ranks 10th out of 14 developing countries. Meanwhile, the teacher component ranks 14th out of 14 developing countries in the world.